What a beautiful morning - Levine, Arthur A., 1962- (Running Press Kids, an imprint of Running Press Book Publishers, 2016)
Every morning is beautiful when Noah visits his Grandparents. When Grandpa and Noah wake up, they take off singing and hardly stop: walking the dog, splashing through puddles, and eating French toast with cinnamon. But one summer Grandpa seems to have forgotten how to do the things they love. Does he even know who Noah is? Grandma steps in energetically, filling in as best she can. But it is Noah who finds the way back to something he can share with Grandpa. Something musical. Something that makes the morning beautiful again. This is a story about how love helps us find even what we think is lost.